2021
DOI: 10.3389/fonc.2021.783480
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of TACE Combined With Lenvatinib Plus Sintilimab in Unresectable Hepatocellular Carcinoma: A Multicenter Retrospective Study

Abstract: ObjectiveTo assess the efficacy and safety of transarterial Chemoembolization (TACE) combined with lenvatinib plus sintilimab in unresectable hepatocellular carcinoma (HCC).Patients and MethodsThe data of patients with unresectable HCC administered a combination therapy with TACE and lenvatinib plus sintilimab were retrospectively assessed. Patients received lenvatinib orally once daily 2 weeks before TACE, followed by sintilimab administration at 200 mg intravenously on day 1 of a 21-day therapeutic cycle aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
57
2

Year Published

2022
2022
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(67 citation statements)
references
References 34 publications
8
57
2
Order By: Relevance
“…This real-world retrospective study showed significantly better overall survival and tumor response rate outcomes with TACE plus apatinib plus camrelizumab than with apatinib plus camrelizumab in patients with unresectable HCC. Cao et al (24) reported TACE combined with lenvatinib and sintilimab for unresectable HCC with a median OS of 23.6 months and ORR of 46.7%, which is similar to our results. These suggest that TACE combined with targeted therapy plus immunotherapy is a promising treatment option in unresectable HCC.…”
Section: Safetysupporting
confidence: 91%
“…This real-world retrospective study showed significantly better overall survival and tumor response rate outcomes with TACE plus apatinib plus camrelizumab than with apatinib plus camrelizumab in patients with unresectable HCC. Cao et al (24) reported TACE combined with lenvatinib and sintilimab for unresectable HCC with a median OS of 23.6 months and ORR of 46.7%, which is similar to our results. These suggest that TACE combined with targeted therapy plus immunotherapy is a promising treatment option in unresectable HCC.…”
Section: Safetysupporting
confidence: 91%
“…Therefore, the combination of TACE, lenvatinib and PD-1 inhibitor may bring about a synergistic antitumor activity, contributing to improved clinical outcomes in advanced HCC patients. Previous studies (29,30) have assessed the combination of TACE, lenvatinib and PD-1 inhibitor for patients with unresectable HCC and reported a PFS of 11.4-13.3 months and an OS of 23.6-24.0 months, which seemed much longer than those for the patients treated with TACE-L-P in our study. However, it was worth noting that these studies enrolled a large proportion (25.0%-54.5%) of patients with HCC at BCLC stage B, who were expected to achieve better outcomes than those with BCLC stage C HCC in the present study.…”
Section: Discussioncontrasting
confidence: 49%
“…PFS at 0.5, 1, 1.5, and 2 years were evaluated in 13 ( 21 , 25 , 31 38 , 40 42 ), 13 ( 21 , 25 , 31 38 , 40 42 ), 11 ( 21 , 25 , 31 37 , 41 , 42 ), and 5 studies ( 21 , 32 , 34 , 37 , 42 ), and the pooled rates and 95%CI were 0.781 (0.688-0.862), 0.387 (0.293-0.486), 0.117 (0.076-0.165), and 0.069 (0.005-0.182), respectively ( Table 3 ). OS at 0.5, 1, 1.5, 2, and 3 years were evaluated in 12 ( 21 , 25 , 31 36 , 39 42 ), 12 ( 21 , 31 34 , 39 42 ), 12 ( 21 , 31 34 , 39 42 ), 9 ( 21 , 31 34 , 39 42 ), and 5 studies ( 21 , 31 33 , 42 ), and the pooled rates and 95%CI were 0.943 (0.902-0.975), 0.690 (0.585-0.786), 0.385 (0.246-0.533), 0.212 (0.117-0.324), and 0.056 (0.028-0.091), respectively ( Table 3 ).…”
Section: Resultsmentioning
confidence: 99%